2014
DOI: 10.1037/fam0000032
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to family environment: BDNF Val66met and 5-HTTLPR influence depressive symptoms.

Abstract: Functional genetic polymorphisms associated with Brain-Derived Neurotrophic Factor (BDNF) and serotonin (5-HTTLPR) have demonstrated associations with depression in interaction with environmental stressors. In light of evidence for biological connections between BDNF and serotonin, it is prudent to consider genetic epistasis between variants in these genes in the development of depressive symptoms. The current study examined the effects of val66met, 5-HTTLPR, and family environment quality on youth depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
(64 reference statements)
1
26
1
Order By: Relevance
“…The assessment of alternative G × E models supported a strong differential susceptibility model, suggesting that BDNF Met carriers are both able to benefit from better childhood care (as indicated by low CECA.Q scores) and more vulnerable to child maltreatment. This complements previous results related to depression, which showed that the BDNF Met allele is associated both with the lowest and the highest vulnerability to depression depending on the quality of family environment (Dalton et al ) and the history of child maltreatment (Frodl et al ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The assessment of alternative G × E models supported a strong differential susceptibility model, suggesting that BDNF Met carriers are both able to benefit from better childhood care (as indicated by low CECA.Q scores) and more vulnerable to child maltreatment. This complements previous results related to depression, which showed that the BDNF Met allele is associated both with the lowest and the highest vulnerability to depression depending on the quality of family environment (Dalton et al ) and the history of child maltreatment (Frodl et al ).…”
Section: Discussionsupporting
confidence: 89%
“…It has been recently argued that genotypes may be associated with differential susceptibility to environment, resulting in both greater costs from environmental adversity and greater benefits from environmental support (Belsky & Pluess ; Belsky et al ). This hypothesis has been supported in the case of the BDNF Val66Met polymorphism and family environment, with Met carriers showing higher depressive symptoms in negative family environment and lower depressive symptoms in positive family environments (Dalton et al ). Similarly, a reduced volume of hippocampal regions, which had been associated with depression, was found in BDNF Met allele carriers with a history of child maltreatment, whereas a larger volume was observed in non‐maltreated people with the same genotype (Frodl et al ).…”
Section: Introductionmentioning
confidence: 86%
“…Although this is a relatively small sample, larger samples have also found different interaction models to emerge based on seemingly minor changes in methodology (e.g. Dalton et al, ; Ludmer et al, ; Roisman et al, ). As argued by Del Giudice (), statistical classifications of interaction type have several limitations (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…One well-studied SNP in the BDNF gene is the valine to methionine substitution at codon 66 (val66met). Evidence indicates that BDNF val66met plays a role in depressive symptoms in children and adolescents (Dalton, Hammen, Najman, & Brennan, 2014) as well as cognitive response style (Hilt, Sander, Nolen-Hoeksema, & Simen, 2007; Stone et al, 2013). Of the relatively few studies examining the BDNF val66met polymorphism in relation to cognitive response style, two indicated that the Val/Val genotype was associated with higher rumination in late childhood and early adolescence (Hilt et al, 2007; Stone et al, 2013).…”
Section: Partial Replication Of Two Rumination-related Candidate Genementioning
confidence: 99%